2016
DOI: 10.1103/physrevc.94.054005
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Monte Carlo calculations of two neutrons in finite volume

Abstract: Ab initio calculations provide direct access to the properties of pure neutron systems that are challenging to study experimentally. In addition to their importance for fundamental physics, their properties are required as input for effective field theories of the strong interaction. In this work, we perform auxiliary-field diffusion Monte Carlo calculations of the ground and first excited state of two neutrons in a finite box, considering a simple contact potential as well as chiral effective field theory int… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…The GFMC method has been used to study the ground state of light nuclei employing local chiral interactions [20][21][22][23][25][26][27][28][29]. The same potentials have been used in AFDMC calculations of pure neutron systems, ranging from few-body systems [30][31][32] to pure neutron matter [20][21][22]. More recently, the first AFDMC study of p-shell nuclei employing local chiral interactions has been reported [33].…”
Section: Introductionmentioning
confidence: 99%
“…The GFMC method has been used to study the ground state of light nuclei employing local chiral interactions [20][21][22][23][25][26][27][28][29]. The same potentials have been used in AFDMC calculations of pure neutron systems, ranging from few-body systems [30][31][32] to pure neutron matter [20][21][22]. More recently, the first AFDMC study of p-shell nuclei employing local chiral interactions has been reported [33].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, however, it was realized that all sources of nonlocality can be removed up to next-to-next-toleading order (N 2 LO) in the standard Weinberg power counting. This led to the development of local chiral interactions and their implementation in QMC methods [19,[24][25][26][27] and has allowed for the first QMC studies of light nuclei, neutron matter, and other light neutron systems with chiral EFT interactions at N 2 LO including 3N interactions [28][29][30][31][32]. In this paper, we provide details for the calculations of light nuclei and present additional results.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26]) and as two nucleons using QMC methods in Ref. [27]. These results are directly tied to the phase shifts of the neutron-neutron interaction via the Lüscher formula.…”
Section: Results For N = 3 Andmentioning
confidence: 92%